Influence of Genetic Admixture Components on CYP3A5*3 Allele-Associated Hypertension in Amerindian Populations From Northwest Mexico - Galaviz-Hernández, Carlos; Lazalde-Ramos, Blanca P.; Lares-Assef, Ismael; Macías-Salas, Alejo; Ortega-Chavez, Margarita A.; Rangel-Villalobos, Héctor; Sosa-Macías, Martha (Frontiers in Pharmacology, 2020)
CYP3A5 metabolize endogenous substrates and ~30% of the prescribed drugs. CYP3A5 gene contains an active CYP3A5*1 allele, and a non-functional version, the CYP3A5*3, with consequences in drug therapeutic response and side effects. Both CYP3A5*1 and *3 have been associated with hypertension. The frequency of CYP3A5*3 varies between populations with different ancestry, being Europeans the group with the highest frequency (>90%). Given the importance of CYP3A5*3 in the response to drugs and hypertension development, the aim of the present study was to evaluate the frequency of this polymorphism and its association with hypertension in vulnerable indigenous populations in Mexico. A total of 372 subjects were recruited from 8 ethnic groups of Northwest Mexico. Systolic (SBP), diastolic (DBP) and median (MBP) blood pressure as well as Body Mass Index (BMI) were measured. Ancestry was evaluated through STR analysis; the CYP3A5*1/*3 polymorphisms were identified by Real Time PCR with TaqMan probes. A higher frequency of CYP3A5*1 and *3 was observed in groups with higher (>90%) and lower (<90%) Amerindian ancestry. The CYP3A5*3/*3 genotype was more frequent in indigenous women with higher values of SBP and DBP. On the other side, the *1 allele presented a protective effect for high SBP (OR 0.38, 95% CI 0.17-0.83, p=0.001) and DBP (OR 0.38, 95% CI 0.18-0.81, p=0.007), which remain significant after adjusting by BMI and age, for diastolic (OR 0.38, 95% CI 0.17-0.84, p=0.011) and systolic (OR 0.33, 95% CI 0.15-0.76, p=0.005) BP levels, in women. So, the frequency of CYP3A5*3 varies between groups and seems to depend of ancestry, and CYP3A5*1 decreases the risk of hypertension on Mexican indigenous women. The population analysis of CYP3A5*1/*3 has profound implications not only for the susceptibility to diseases such as hypertension but also for a safer drug administration regime, assuring a better therapeutic response and less side effects.